Incidencia de los ejercicios de coordinación óculo-manual en la técnica de la recepción del voleibol en los estudiantes de 7mo año de la Escuela de Educación Básica Particular “Siglo XXI”, Loja, 2024 - Cuenca Poma, Marjorie Elizabeth (2025)
The current Curricular Integration Work was carried out with the objective of analyzing the incidence of hand-eye coordination exercises in the technique of volleyball reception in 7th grade students of the Escuela de Educación Básica Particular “Siglo XXI” of the city of Loja, period 2024, research has a mixed approach, descriptive and exploratory type, and non-experimental design. Also, diagnostic instruments were used, such as an interview with the physical education teacher and two observation guides for 11 students under study. After the application of the research instruments, it was established that the seventh year students present several problems in coordination and in the technical gesture of volleyball reception. Likewise, it could be observed that most of the students have some difficulties in the technique and efficiency of receiving the ball inside the court in the different zones. On the other hand, in the execution of the reception technique with forearms it was evidenced that 55% of the students do not perform a correct position of the hands and displacements, in the same way this same amount does not perform a correct position of the elbows and shoulders, and this same percentage does not perform the contact of the ball with the surface of the forearms, while 64% of the students do not stretch the joints of the feet, knees and hips. These results show that a large part of the student population analyzed have difficulty in executing the volleyball reception technique due to the lack of hand-eye coordination. Based on these results, a proposal of exercises of hand-eye coordination was designed, which is structured in 16 class sessions with dynamic activities that seek to influence the technique of volleyball reception